Mass Transfer from Flat Plates to Power-Law Fluids In Laminar Flow - Ghosh U.K.; Gupta S.N.; Kumar S.; Upadhyay S.N.; Dey K.N. (My University, 2025)
Mass transfer from vertical flat plates to water and 0.5 to 1.5% aqueous CMC solutions is measured in the Reynolds number range of 10–2 to 6.0 x 103. Blasius analysis has been found to be valid only up to a Reynolds number of 100, below which Graetz-Leveque solution is more appropriate. © 1986, Taylor & Francis Group, LLC. All rights reserved.